Lingkar Rupa Community Strategy in Developing the Actualization of Street Artists in Kota Tua, Jakarta - Fransisca Retno Setyowati Rahardjo (Graduate School of Institut Seni Indonesia Yogyakarta, 2022)
This study will describe the method used by the initiators of the Lingkar Rupa Community as a basis for a strategy to develop the quality of the work of street artists in Kota Tua, as well as a description that archives the movement of a new art community in Jakarta. Lingkar Rupa in an effort to protect and actualize themselves and the work of street artists in Kota Tua. The community, which was initiated by an art and culture teacher, Ferry Kurniawan, is a social activity that arose from the founder's personal anxiety about art life at the grassroots level. This research will discuss the background, art activities and exhibitions, art strategies and the impact that Lingkar Rupa has carried out. With a qualitative method, namely using in-depth interview techniques from several founders and members of Lingkar Rupa's own informants. The theory of participatory art will be a surgical tool that examines the direction of this community's journey. It should be noted that the 'street art' that the author describes here is an art that is different from the terminology of 'street art' in the West which often emerges from elite academic circles and tries to present works of protest against the social situation around them in a very 'educated' manner. This research is also important to identify the 'underground' movement which is often not recognized because it is less popular and dapper. Strategi Komunitas Lingkar Rupa dalam Mengembangkan Aktualisasi Seniman Jalanan di Kota Tua, JakartaAbstrakPenelitian ini akan mengurai metode apa yang dipakai oleh penggagas Komunitas Lingkar Rupa sebagai dasar strategi mengembangkan kualitas berkarya para seniman jalanan di Kota Tua, selain sebagai deskripsi yang mengarsipkan gerakan sebuah komunitas seni baru di Jakarta. Lingkar Rupa dalam upaya mengayomi dan mengaktualisasi diri dan kekaryaan para seniman jalanan di Kota Tua. Komunitas yang digagas oleh seorang guru seni dan budaya, Ferry Kurniawan, merupakan aktivitas sosial yang muncul dari kegelisahan personal pendirinya mengenai kehidupan seni di kalangan akar rumput. Dalam penelitian ini akan dibahas mengenai latar belakang, kegiatan seni dan pameran, strategi kesenian, serta dampak yang telah Lingkar Rupa kerjakan, dengan metode kualitatif yaitu menggunakan teknik wawancara yang mendalam dari beberapa informan pendiri dan anggota Lingkar Rupa itu sendiri. Teori seni partisipatoris akan menjadi alat bedah yang mengkaji arah perjalanan komunitas ini. Perlu diketahui bahwa ‘seni jalanan’ yang penulis jabarkan di sini adalah seni yang berbeda dari terminologi ‘street art’ di Barat yang kerap kali muncul dari kalangan akademi elit dan mencoba menghadirkan karya protes terhadap situasi sosial di sekitarnya dengan sangat ‘terdidik’. Penelitian ini juga penting untuk mengidentifikasi gerakan ‘bawah tanah’ yang sering kali tidak terekognisi karena kurang populer dan necis.